PENGARUH MEDIA JERUK BALI MELALUI PENDEKATAN PMRI MATERI LUAS DAN KELILING BANGUN DATAR KELAS VI: The Influence of Grapefruit Media through the PMRI Approach, Area and Perimeter of Flat Buildings for Class VI - Kusumaningrum, Sabrina Ratih; Prasetya, Arif Budi; Zuliana, Eka (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
This research aims to investigate the influence of using Bali orange media through the Realistic Mathematics Education (PMRI) approach on the subject of area and perimeter of flat shapes among sixth-grade students at SDN 7 Gondosari. The research method employed is quantitative descriptive. The sample was obtained using Nonprobability Sampling technique with a total sampling method, involving a population of 36 students, which also represents the sample size in this study. The data collection instrument used was a test. Data collection techniques involved observation, tests, and documentation. The research findings indicate that the average learning outcome, previously at 50, increased to 70. Therefore, the use of Bali orange media influences students' learning outcomes.